2020
DOI: 10.1088/1361-6463/ab7627
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory growth effect of lightning strikes applied in the vicinity of shiitake mushroom bed logs

Abstract: Since ancient times, the anomalous occurrence of mushrooms has been observed in and around locations struck by lightning. Based on this phenomenon, various cultivation techniques using a high voltage to cultivate shiitake mushroom in bed log (wood) have been proposed. Undoubtedly, the fruiting capacity of shiitake mushrooms is significantly promoted by direct application of a high voltage to the cultivation bed logs. However, mushroom bed logs are rarely struck directly by lightning in the natural environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The research of Shimizu et al, which treated mushrooms indirectly by simulating lightning, revealed that the yield of mushrooms improved along with increased energy that imposes on the culture medium within reasonable limits [31]. The possible reasons were mainly the effect of the electric field and pressure waves generated owing to the thermal expansion of air during lightning strikes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Shimizu et al, which treated mushrooms indirectly by simulating lightning, revealed that the yield of mushrooms improved along with increased energy that imposes on the culture medium within reasonable limits [31]. The possible reasons were mainly the effect of the electric field and pressure waves generated owing to the thermal expansion of air during lightning strikes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shimizu et al simulated natural lightning using a pulse voltage generator and stimulated shiitake mushroom logs without direct lightning application to the cultivated bed logs. They found that lightning promoted the growth of mushrooms [31]. Therefore, based on these investigations, we aimed to study the possible effect of plasma treatment on the growth of G. lucidum.…”
Section: Introductionmentioning
confidence: 99%
“…Singer.) fruit body formation (Shimizu et al, 2020; Takaki et al, 2010); the authors hypothesized that stress caused by these mechanical stimuli triggered fungi to disperse away from an inappropriate habitat. In addition, Japanese mushroom farmers beat shiitake mushroom logs or beds to accelerate fruit body formation (Ito, 1964).…”
Section: Figurementioning
confidence: 99%
“…Shimizu et al reported the improvement of harvest yielding of mushroom (L. edodes) by stimulation using shockwave generated by long-gap pulse arc discharge (Shimizu et al 2020). The artificial lightning impulse voltage was generated by an impulse voltage generator (IG), was applied to rod type high-voltage electrode to generate long-gap discharge.…”
Section: Effect Of High-voltage Stimulation In Bed-log Cultivationmentioning
confidence: 99%